2004
DOI: 10.1111/j.1471-1842.2004.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the information management and technology training needs of doctors in an acute NHS trust in the United Kingdom

Abstract: Both junior and senior doctors have basic computer literacy, but nearly half of this population identify the use of database software as a training need. In addition, there are several health informatics topics of which a large proportion of doctors, particularly the juniors, have little knowledge, but which have not been identified as training needs. Some recommendations are made for provision of in-house health informatics education for doctors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 8 publications
3
21
0
1
Order By: Relevance
“…Most students reported using the Internet to find information for assignments and projects, and this was the most common use of ICT at university by a margin of more than 20%, which is in agreement with at least one UK-based study (Devitt & Murphy, 2004). The fact that students are using the Internet to find information should be seen as a positive step towards self-directed learning.…”
Section: Discussionsupporting
confidence: 80%
“…Most students reported using the Internet to find information for assignments and projects, and this was the most common use of ICT at university by a margin of more than 20%, which is in agreement with at least one UK-based study (Devitt & Murphy, 2004). The fact that students are using the Internet to find information should be seen as a positive step towards self-directed learning.…”
Section: Discussionsupporting
confidence: 80%
“…There is concern that those who trained before the so-called information age will be inadequately equipped for their work. 10 Computer knowledge was highest among doctors and lowest among nurses. Only 22.7% of the healthcare professionals had good computing skills.…”
Section: Introductionmentioning
confidence: 97%
“…In one UK study, 44% of hospital doctors identified no skills in database software and saw this as a training need. 11 Another UK study found that computer skills among one group of trainee doctors was 'low', 12 and in a group of UK nursing staff, infrequent use of IT provision was evident, despite their having a 'positive attitude' to IT. 13 One study among Australian general medical practitioners has shown that older GPs (>55 years) have found greater change in their skills after training than their younger colleagues.…”
Section: Discussionmentioning
confidence: 99%